Evaluation of a crystallographic surrogate for kallikrein 5 in the discovery of novel inhibitors for Netherton syndrome. Issue 5 (2nd May 2019) - Thorpe, James H.; Edgar, Emma V.; Smith, Kathrine J.; Lewell, Xiao Q.; Rella, Monika; White, Gemma V.; Polyakova, Oxana; Nassau, Pamela; Walker, Ann L.; Holmes, Duncan S.; Pearce, Andrew C.; Wang, Yichen; et al.
Abstract : The benzamidine‐derived ligand GSK144 inhibits the target enzyme kallikrein 5 (KLK5) with a pIC50 of 7.1. X‐ray crystallography of KLK5 proved challenging, with the only structure solved being that with GSK144. To enable structure‐guided design in support of medicinal chemistry, a KLK6‐derived crystal system was developed. Here, a biochemical pharmacological assessment of the KLK6 surrogate enzymes compared with KLK5 is described and details of the X‐ray structures obtained with GSK144 are discussed. Abstract : The inhibition of kallikrein 5 (KLK5) has been identified as a potential strategy for treatment of the genetic skin disorder Netherton syndrome, in which loss‐of‐function mutations in the SPINK5 gene lead to down‐regulation of the endogenous inhibitor LEKTI‐1 and profound skin‐barrier defects with severe allergic manifestations. To aid in the development of a medicine for this target, an X‐ray crystallographic system was developed to facilitate fragment‐guided chemistry and knowledge‐based drug‐discovery approaches. Here, the development of a surrogate crystallographic system in place of KLK5, which proved to be challenging to crystallize, is described. The biochemical robustness of the crystallographic surrogate and the suitability of the system for the study of small nonpeptidic fragments and lead‐like molecules are demonstrated.